Gender diversity in the boardroom and firm performance of Malaysian public listed companies - Mohamad Khudzari, Julizaerma; Muhamad Sori, Zulkarnain (Elsevier, 2012)
The lack of women representation on boards become an important issue recently that need to be addressed due to the benefits driven from gender diversity in the boardrooms. This study intends to examine the association between gender diversity in the board of directors and firm performance. The discovery on content analysis is used to collect the data. The population of the study comprises of the companies listed in Bursa Malaysia for both Main and ACE market for the year 2008 and 2009. Quota and simple random sampling techniques were used in order to get an adequate representation of women. The data is analyzed using ordinary least square regression method to determine the association of the variables. The finding indicates that a positive association exists between gender diversity and firm performance. This suggests that women directorship may influence firm performance.